Take half of the coefficient of x: It is 3, and half that is 3/2.
Then <span>x^2+3x=6 becomes:
</span><span> x^2+3x + (3/2)^2 =6 + (3/2)^2, and
(x+3/2)^2 = 6 + 9/4
You were not asked to solve the equation, but why not do it for the practice?
</span>Solve (x+3/2)^2 = 6 + 9/4 for x. There will be 2 values.
Answer:
-164x^2
Step-by-step explanation:
The Perimeter of a square is 4s where s is the length of 1 side.
So P=4(-41x^2) 41*4=164 ----> P=-164x^2
The answer is <span>5, 4, 2
</span>
Among all choices we have 5, so
x = 5
x - 5 = 0
Let's divide the expression by (x - 5) using the long division:
x³ - 11x² + 38x - 40
(x - 5) * x² = x³ - 5x² Subtract
____________________________
-6x² + 38x - 40
(x - 5) * (-6x) = -6x² + 30x Subtract
____________________________
8x - 40
(x - 5) * 8 = 8x - 40 Sutract
____________________________
0
Thus: x³ - 11x² + 38x - 40 = (x - 5)(x² - 6x + 8)
Now, let's simplify x² - 6x + 8.
x² - 6x + 8 = x² - 2x - 4x + 8 =
= x² - 2*x - (4*x - 4*2) =
= x(x - 2) - 4(x - 2) =
= (x - 4)(x - 2)
Hence:
x³ - 11x² + 38x - 40 = (x - 5)(x - 4)(x - 2)
To calculate zero:
x³ - 11x² + 38x - 40 = 0
(x - 5)(x - 4)(x - 2) = 0
x - 5 = 0 or x - 4 = 0 or x - 2 = 0
x = 5 or x = 4 or x = 2
Answer:
B
Step-by-step explanation:
When a polynomial is in standard form, it is arranged in the order of largest power first, followed by the next largest, and then so on. The only polynomial here that follows this rule is the second one, or choice B. Hope this helps!